Planning a digital intervention for adolescents with asthma (BREATHE4T): A theory‐, evidence‐ and Person‐Based Approach to identify key behavioural issues. Issue 11 (6th September 2022) - Easton, Stephanie; Ainsworth, Ben; Thomas, Mike; Latter, Sue; Knibb, Rebecca; Cook, Amber; Wilding, Sam; Bahrami‐Hessari, Michael; Kennington, Erika; Gibson, Denise; Wilkins, Hannah; Yardley, Lucy; et al.
Abstract: Objectives: To describe a transparent approach to planning a digital intervention for adolescents to self‐manage their asthma using breathing retraining (BRT), based on an existing, effective adult intervention (BREATHE). Methods: A theory‐, evidence‐, and Person‐Based Approach was used to maximise the effectiveness and persuasiveness of the intervention. A scoping review and semistructured interviews with target intervention users ( N = 18, adolescents aged 12−17 years with asthma and parents) were carried out to explore user perspectives, barriers, and facilitators towards the intended behaviours and potential intervention features. The combined evidence was used alongside and to inform theory‐based activities and enabled iterative planning of the intervention. Results: The scoping review identified themes relating to user‐specific self‐management issues, content, education, training needs, and features for a digital intervention. Interviews elicited potential barriers to intended behaviours such as the anticipated embarrassment of using BRT and concerns around remaining calm. Facilitators included BRT delivered by adolescents who share experiences of asthma and information for performing exercises discreetly. Relevant theoretical frameworks ensured that appropriate psychological constructs were targeted. A behavioural analysis identified six intervention functions and thirty behaviour change techniques. Logic modelling mapped the programme theory and mechanisms, which aims to improve adolescent asthma‐related quality of life. Conclusions: This study gives a transparent insight into the approach followed to plan a self‐guided BRT intervention for adolescents and has led to identification of key behavioural issues, enabling relevant intervention content to be chosen. Insight has been given into adolescent perceptions of BRT, which facilitated development of the prototype intervention.